2002
DOI: 10.4049/jimmunol.169.6.3046
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Immunoproteasome Subunit Expression In Vivo Following Pathogenic Fungal Infection

Abstract: The proteasome catalytic β subunits LMP2, LMP7, and MECL-1 and two proteasome activator proteins, PA28 α and β, are induced following exposure to IFN-γ in vitro. Induction of these immunosubunits and the PA28 α/β hetero-oligomer alters proteasome catalytic functions and specificity and enhances production of certain MHC class I epitopes. We sought to determine whether and to what extent proteasome subunit composition is regulated in vivo and to elucidate the mechanisms of such regulation. We analyzed basal exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 60 publications
3
58
0
1
Order By: Relevance
“…Although TNF-␣ has been shown to up-regulate ␤1i in human cell lines, either alone or synergistically with IFN-␥ (32,33), no effects on expression of these genes were found in fungal infection of mice (34). Our experiments with cytokine receptor knockout (KO) mice demonstrate that lack of TNF-␣ signaling does not influence the induction of I-proteasome during L. monocytogenes infection.…”
Section: Discussionmentioning
confidence: 67%
“…Although TNF-␣ has been shown to up-regulate ␤1i in human cell lines, either alone or synergistically with IFN-␥ (32,33), no effects on expression of these genes were found in fungal infection of mice (34). Our experiments with cytokine receptor knockout (KO) mice demonstrate that lack of TNF-␣ signaling does not influence the induction of I-proteasome during L. monocytogenes infection.…”
Section: Discussionmentioning
confidence: 67%
“…Hepatic 20S proteasomes have an extraordinarily long half-life of 12 to 15 days, as demonstrated in metabolically labeled rats (66), indicating that the replacement of constitutive proteasomes by immunoproteasomes in MCMV-infected livers occurs surprisingly fast. A strong increase in immunoproteasome formation has also been documented in the livers of mice during viral, bacterial, and fungal infections with LCMV, Listeria monocytogenes, and Histoplasma capsulatum (6,39). This effect was markedly reduced in IFN-␥-deficient mice, indicating that this cytokine is indeed a leading factor driving proteasome replacement in vivo (39).…”
Section: Discussionmentioning
confidence: 78%
“…3A). (39). Western blot analyses revealed that the proteasome isolated from A2K b mice contained indeed the three subunits LMP2, LMP7, and MECL-1 (Fig.…”
Section: Resultsmentioning
confidence: 99%